Influence of management factors on reproduction in beef cattle: 1. Effects of melengestrol acetate and growth promoting implants on oocyte quality and subsequent in vitro embryo development 2. Exposure of prepubertal beef bulls to cycling females to enhance sexual development - Miller, Natalie Ann (Kansas State University, 2012)
This thesis involves two separate studies that evaluate the effects of different beef cattle management practices on reproduction. The objective of the first study was to determine if feedlot heifers administered melengestrol acetate (MGA) and growth promoting implants could serve as viable oocyte donors for in vitro embryo production. Ovaries from heifers administered MGA and growth promotants (MGA-Implant) and ovaries from heifers not administered either substance (Control) were collected from heifers post-slaughter. Oocytes were harvested and in vitro maturation, in vitro fertilization (IVF), and in vitro culture were completed. Treatment and time interacted to affect the number of oocytes aspirated per ovary (P = 0.07) and the number of zygotes per ovary (P = 0.07). Fertilization (P = 0.90) and cleavage rates (P = 0.80) did not differ between treatments. Blastocyst rates (P = 0.30) and the number of embryos per ovary (P = 0.50) did not differ between treatments. We concluded that beef feedlot heifers fed MGA and implanted with growth promotants seem to be a viable source of oocytes for in vitro embryo production. In the second study, we hypothesized that continuous fenceline exposure of prepubertal beef bulls to cycling beef females would hasten the onset of puberty as well as increase the percentage of bulls passing their initial breeding soundness examination (BSE). Bulls were either exposed to estrous females (exposed) or were not exposed (control). Monthly scrotal circumference (SC) measurements, blood samples, semen evaluations, and bull behavior assessments were conducted. Age at puberty (P = 0.40), SC at puberty (P = 0.50), and weight at puberty (P = 0.30) did not differ between treatments. A similar (P = 0.50) percentage of bulls passed their initial BSE at 363 ± 21.5 d of age (exposed: 87.8%; control: 74.2%). Treatment, month, and stage of the estrous cycle of cows interacted to affect the number of mount attempts (P = 0.05) and the number of flehmen responses (P < 0.001). In conclusion, bulls given continuous fenceline exposure to cycling beef females were neither younger at puberty nor did a greater percentage pass their initial BSE.
Keywords: Beef cattle; Reproduction; In vitro fertilization; Bulls; Animal Sciences (0475)